2013
DOI: 10.28945/1901
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Underrepresented Students of Color for Doctoral Success: The Role of Undergraduate Institutions

Abstract: Since the late 1980s, there has been a significant increase in the number of doctoral degrees conferred upon underrepresented minority (URM) students. However, White students still account for the vast majority -approximately 80 percent -of all doctoral degrees conferred in the United States. As education stakeholders seek to diversify the professoriate, an updated examination of the baccalaureate origins of successful URM students is warranted to improve our understanding of where they are best prepared for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 49 publications
(81 reference statements)
0
25
0
Order By: Relevance
“…Salters’ (1997) findings as reported by Lundy‐Wagner et al (2013) indicate that African American, Asian/Pacific Islander, and Latina/o doctoral students receive fewer teaching and research assistantships than their White counterparts. Other studies reported have shown that foregone research and teaching opportunities for URMs can limit their scholarship and/or persistence, which are necessary for progression into faculty roles (Antonio, 2002; Ellis, 2001; Margolis and Romero, 1998).…”
Section: Review Of the Literaturementioning
confidence: 90%
See 3 more Smart Citations
“…Salters’ (1997) findings as reported by Lundy‐Wagner et al (2013) indicate that African American, Asian/Pacific Islander, and Latina/o doctoral students receive fewer teaching and research assistantships than their White counterparts. Other studies reported have shown that foregone research and teaching opportunities for URMs can limit their scholarship and/or persistence, which are necessary for progression into faculty roles (Antonio, 2002; Ellis, 2001; Margolis and Romero, 1998).…”
Section: Review Of the Literaturementioning
confidence: 90%
“…According to a 2013 report by the NCES, HBCUs educated 16% or more of all African American undergraduates despite representing only 3% of all postsecondary institutions (Lundy‐Wagner, 2015). Historically Black colleges and universities are also well known for greater diversity of college and university faculties (Lundy‐Wagner et al, 2013; Perna, 2001). Perna (2001) found that 9% of full‐time African American faculty earned their doctorates from HBCUs and that more than half of them returned to their degree‐granting institution as teaching faculty.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…HBCUs are also well known for diversifying various professional fields; the contribution of HBCUs in preparing Black doctoral degree recipients and college and university faculty is well known (Lundy‐Wagner, Vultaggio, & Gasman, ; Perna, ). The role of HBCUs in Black teacher preparation (Gasman et al., ) and in increasing the number of Blacks in the science, technology, engineering, and mathematics (STEM) pipeline is also notable (Lundy‐Wagner, ; Perna et al., ).…”
Section: College Access and Diversitymentioning
confidence: 99%